KEFAHAMAN MENGENAI ‘IDDAH DI KALANGAN PELAJAR WANITA POLITEKNIK UNGKU OMAR, IPOH, MALAYSIA - Halim, Nabilah Hasinah; Ahmad, Che Maryam (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
This study is conducted to investigated level of understanding among the female students of Politeknik Ungku Omar, Ipoh about 'Iddah (waiting period before a widow or divorced woman may remarry). One set of the questionnaires contains 36 items was distributed to 31 respondents. Data gained from the respondents was analyzed using the Statistical Package For Social Sciences (SPSS) version 23 for further statistical analysis. The analysis showed the value of alpha Cronbach of this research tool was a=0.723. Research finding that the majority of respondents have a high level of understanding of ?Iddah with an average overall score of 3.69 min. This suggests that female students at the Polytechnic Ungku Omar mostly very understanding. As such, this understanding must still be maintained through reading or attending lectures and religious lectures. Thus, spiritually as follow religious lectures in addition to increasing the scientific literature is important in helping to understand the tenets of marriage.